Pengaruh penjaminan mutu keselamatan pasien terhadap tindakan keselamatan pasien di RS Bhakti Yudha Depok. - Iswati, (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Head nurse has the accountability to challenge any act that appears unsafe. The research was aimed to explore the influence of patient safety quality assurance by head nurse to the implementing of clinical nurses on patient safety at Bhakti Yudha Depok Hospital. The method used in this study was quasi experiment design: Non equivalent control group with 120 clinical nurse as the sample divided into the intervention and control group, 60 participants respectively. The results revealed that there was a significant influence to the the clinical nurse who got patient safety quality assurance by head nurse which were: Patient identification, efective communication, the correct drug administration, preventing the risk of patient falls, and hand hygiene (p= 0.01, α= 0.05), while there was no significant influence in marking the correct side of the body (p= 0.99, α= 0.05). Based on the results it is recommended that the head nurse as the front line of managers in the hospital to improve they role and function in quality assurance of patient safety.Keywords:Head of nurse, patient safety, quality assurance, the clinical nurses on patient safety